Prospective study on comparison between the efficacy of ulipristal acetate and mifepristone in the management of fibroids in the reproductive age group - Anand, Priyam; Hansda, Rani; Bharti, Atima; Murmu, Suchita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Uterine fibroids are the most common benign tumours found in women of reproductive age. Women experience symptoms affecting their quality of life, which include menorrhagia, pelvic pain, and pressure symptoms. In severe cases, fibroid causes infertility and pregnancy complications. Surgical interventions such as hysterectomy and myomectomy are effective, but invasive. Recently, selective progesterone receptor modulators (SPRMs) have emerged for the medical management, which include mifepristone and ulipristal acetate. Methods: This was a prospective, observational clinical cohort study that enrolled 132 women, 66 in each group of ulipristal and mifepristone, conducted over a period of 18 months. Eligible participants were identified from the Outpatient Department at RIMS. Results: After treatment, Hb levels increased to 9.9 g/dl (13.8% increase) with Ulipristal acetate and 10.4 g/dl (14.3% increase) with Mifepristone (p<0.001). The findings indicate a significant improvement in Hb levels with both treatments, with Mifepristone showing a slightly greater increase. Before treatment, both groups had a similar mean endometrial thickness of 5.8 mm (p=0.5471). After treatment, thickness increased significantly to 7.2 mm in the Ulipristal acetate group and 8.7 mm in the Mifepristone group (p=0.001). Conclusions: Mifepristone (25 mg) may be preferable for patients with larger-sized fibroids and anemia. Ulipristal Acetate (5 mg) is beneficial for women having menorrhagia. Endometrial thickness should be regularly assessed in patients. Liver function tests (LFTs) should be performed periodically, particularly for Ulipristal Acetate users.